O processo de desenvolvimento das redes interorganizacionais - Alves, Juliano Nunes (2016)
The present study aims to understand the process of interorganizational networks development and to move forward as theoretically as empirically on management field of networks. The interorganizational networks were here studied by the theory of process of Van de Ven (1992), Van de Ven & Poole (1995) and Halinen (1998) that, for abiding different procedures is used in an integrated way, the theories of the life cycle, evolutionary, teleology and dialectics as a means to understanding of duality (static / dynamic) of organizational structures of events that occurs over time. In a sequential manner and supported in different schools or perspectives of networks, we aim to understand the events occurred in the networks over time, and provide a vision of how the development process and changes happens in interorganizational networks. The research was conducted by a multicases, qualitative and exploratory study carried out through narratives and focused interviews, by a procedural approach in eight interorganizational networks, located in Rio Grande do Sul. Events arising from the actions of key network individuals were analyzed. Considering the need to link between theory, empirical phenomena and the methodology used in the research, it was adopted the abductive approach with content analysis of the data. In the results, has been examined and described each case, featuring different evolutions, but with the possibility in a general context to be treated in a complementary manner. It is considered that the program "Redes de Cooperação " was crucial to raising awareness and encourages the formation of networks. Over time, the actions of the teams provided by the program have demonstrated the need for restructuring to bring all members to the interests of the network, overcoming individual interests of participation and gain the acceptance of the other members. Another required restructuring was the network professionalization on the strategy and activities. In such situation, the network becomes in the management of activities more independent people and no more a network member, avoiding the interconnection between individual interests and the network. In this restructuring, the network reaches a perceived crucial point in two of analyzed cases. First, it followed to the professionalization reducing their horizontal nature in which everyone is autonomous and singly they think your individual activities and for them answered reaching to a network more vertical. At the other, the network, in addition to responding for the management of their issues, also has taken the issues of individual processes of each of its members, through brand licensing, standardization process, administration of marketing and communication, selecting a mix of products, elaborating a list of suppliers. Over time and directly in relation of changing events and networks development are teams or working groups that provide benefits management, or expectations of those involved in interorganizational networks. Due to the individual autonomy that characterizes this perspective, it has become possible to integrate the four motors of change and provide a vision of how interorganizational networks can manage as the relationships established and developed in networks with the dialectical theory as the different interests with common goals through of teleological and evolutionary theories. To understand how to manage interorganizational networks, over time, it must be understood how the development process happens and how the different schools and change motors step in overtime on changes and evolution of the network. The studies in networks management can be developed in the future, based on the implications of proposals of this thesis.